2011
DOI: 10.1097/prs.0b013e31822b6456
|View full text |Cite
|
Sign up to set email alerts
|

Nipple-Sparing Mastectomy for Prophylactic and Therapeutic Indications

Abstract: Therapeutic, IV.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
108
1
4

Year Published

2013
2013
2020
2020

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 181 publications
(118 citation statements)
references
References 0 publications
4
108
1
4
Order By: Relevance
“…Although nipple-areola-sparing mastectomy has not been shown to be associated with increased infectious complications, the incidence reported in the literature is as high as 17.8 percent, which is significantly higher than our reported incidence. [26][27][28] Third, when comparing the ready-to-use acellular dermal matrix cohort to the submuscular cohort, breasts were more likely to have greater mean tissue expander size (439.88 ± 117.14 ml versus 396.63 ± 113.41 ml; p = 0.0020), greater mean tissue expander fill (205.99 ± with the submuscular cohort. This, given the clear indications for acellular dermal matrix use in the study, is understandable.…”
Section: Discussionmentioning
confidence: 99%
“…Although nipple-areola-sparing mastectomy has not been shown to be associated with increased infectious complications, the incidence reported in the literature is as high as 17.8 percent, which is significantly higher than our reported incidence. [26][27][28] Third, when comparing the ready-to-use acellular dermal matrix cohort to the submuscular cohort, breasts were more likely to have greater mean tissue expander size (439.88 ± 117.14 ml versus 396.63 ± 113.41 ml; p = 0.0020), greater mean tissue expander fill (205.99 ± with the submuscular cohort. This, given the clear indications for acellular dermal matrix use in the study, is understandable.…”
Section: Discussionmentioning
confidence: 99%
“…August 10, 2014|Volume 5|Issue 3| WJCO|www.wjgnet.com Petit et al [109] 2009 1001 35 55 Nahabedian et al [17] 2006 11 0 1 Spear et al [108] 2011 49 3 3 Voltura et al [50] 2008 51 0 0 De Alcantara Filho et al [23] 2011 341 0 1 Wijayanayagam et al [71] 2008 64 3 10 Jensen et al [27] 2011 127 0 8 Paepke et al [103] 2009 109 1 23 Babiera et al [107] 2010 54 0 4 Munhoz et al [33] 2013 158 1 8…”
mentioning
confidence: 99%
“…We used the following key terms to search all databases: nipple-sparing mastectomy, inframammary fold, immediate reconstruction, skin flap necrosis, nipple necrosis, and reconstructive criteria. The literature reflects a wide range of nipple-areolar complex necrosis rates between 0-48% (Salgarello et al, 2010;Rusby, Smith, & Gui, 2010 Sacchini et al, 2006;Spear et al, 2011;Djohan et al, 2010;Crowe et al, 2004;Colwell et al, 2014;Salibian, Harness, & Mowlds, 2013;Endara, Chen, Verma, Nahabedian, & Spear, 2013 reconstruction, Gould et al (2013) found that their overall incidence of any (partial or total) nipple necrosis was 20% via a non-IMF approach. In a review of 64 NSM via various approaches, Wijayanayagam et al noted a total NAC necrosis rate of 20%, partial NAC necrosis 84%, and total skin-sparing skin flap necrosis of 17%.…”
Section: Discussionmentioning
confidence: 99%